Civil Society and Disarmament 2013 - United Nations (United Nations, 2013)
This publication contains the statements by representatives of non-governmental organizations that were delivered from 14 to 23 May 2013 during the informal thematic discussions at the meeting, held in Geneva, of the Open-ended Working Group to develop proposals to take forward multilateral nuclear disarmament negotiations for the achievement and maintenance of a world without nuclear weapons.